Peningkatan Kemampuan Sumber Daya Manusia Dalam Menunjang Efektivitas Kerja Pegawai Pada Kantor Camat Dangia Kabupaten Kolaka Timur - Karlina, Anita; Aminuddin, Aminuddin; Purwati, Ninik Endang (REZ PUBLICA, 2021)
This study aims to identify and describe the Efforts to Improve the Ability of Human Resources in Supporting the Work Effectiveness of Employees at the Dangia Sub-District Office, East Kolaka Regency. This type of research is qualitative research with data collection techniques using observation, interview and documentation techniques. The informants in this study amounted to 5 (five) employees consisting of the Dangia Sub-District Head, the District Secretary, Chief of Section for Government and Public Services, Chief of Section for Community and Village Empowerment, Chief of Section for Development of Peace and Public Order, and a staff of 1 (one) person. The data analysis technique in this research is using the qualitative descriptive analysis technique of the Lexy J method. The results of this study indicate that the Efforts to Increase Human Resource Capability carried out in the Dangia District Office environment are not going well where through the improvement of employee education there is no at all, while for training it has been carried out quite well where there are already several employees who have attended the training but that happened in 2017 alone, it is different with the Head of Dangia Sub-district who every year participates in the training. This of course will support the effectiveness of employees at the Dangia Sub-District Office. Furthermore, the work effectiveness of employees at the Dangia Sub-District Office is partly good even though the education and training of employees is still lacking, this can be seen from the ability to adapt to employees, employee performance, and employee job satisfaction which are carried out well by employees at the Dangia District Office, East Kolaka Regency.